MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN MELALUI KEGIATAN MEMBATIK ECOPRINT DI TK ABA KASIYAN - Sulistioningrum; Ianatuz Zahro; Hendrik Siswono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study uses ecoprint batik to improve the speaking skills of children aged 4-5 years. Kemmis and McTaggart's Classroom Action Research (CAR) paradigm includes preparation, implementation, observation, and reflection in each cycle. The subjects of the study were seven boys and three girls aged 4-5 years at ABA Kasiyan Kindergarten (TK ABA Kasiyan). Direct observation and documentation were used to obtain the data for this study. Children's verbal abilities increased rapidly. In the classroom action research, ecoprint batik playing activities dramatically improved children's speaking skills. In cycle 1, the percentage of children with the criteria